IMPLEMENTASI GAME THEORY PADA PEMILIHAN METODE PEMBELAJARAN YANG TEPAT BAGI TARUNA AAU - Pudjianto, Agus (Akademi Angkatan Udara, 2022)
The Air Force Academy is one of the highest educational institutions in the Indonesian Air Force which is tasked with producing Indonesian Air Force officers who have good personalities, qualified academic abilities, supported by excellent physical abilities in accordance with the slogan